STRATEGI PEMBANGUNAN PERTANIAN DI KAWASAN IBU KOTA NEGARA (IKN) BARU: PERSPEKTIF MULTI-STAKEHOLDER - Rianda Abdi; Ismail Mahmud; Afdil Hafidh; Nurul Kamaliah Umasangaji (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
The relocation of Indonesia’s new capital (IKN) to East Kalimantan presents both opportunities and challenges for the agricultural sector as the foundation of national food security. Agricultural development in this emerging region requires an integrated approach, as food security depends not only on land availability and production capacity but also on supply stability, farmers’ access to inputs, and the long-term sustainability of local production systems. This article analyzes agricultural development strategies in the IKN area and its surrounding regions through a multi-stakeholder perspective involving government, farmers, academics, and students. Using a descriptive qualitative method, data were obtained from a multi-stakeholder dialogue forum in Muara Ulu Jawa Village, Samboja District, as well as secondary data from government documents and academic sources. The findings reveal several key challenges, including limited productive land due to land conversion, shortages of subsidized fertilizers, insufficient agricultural extension officers, and inadequate farm road infrastructure. Stakeholders emphasized the need for farmland protection policies, improved fertilizer distribution, reclamation of former mining sites for new agricultural land, development of irrigation and farm roads, strengthening GAPOKTAN institutions, and increasing extension personnel. Local leaders also highlighted the urgency for IKN to achieve localized food self-sufficiency, considering that East Kalimantan currently meets only 30% of its food needs. Proposed strategies include increasing production, expanding farmland, modernizing agricultural equipment, stabilizing farm-gate prices, and enhancing farmers’ human resource capacity. Academics and students are expected to support farmer adaptation through knowledge transfer, field assistance, and applied research. This study concludes that agricultural development in IKN requires integrated, sustained collaboration among farmers, local governments, the IKN Authority, and universities to align production needs, input access, farmer welfare, and land protection. Such collaboration can position IKN’s agriculture as a long-term food security model for Eastern Indonesia.